Strategies for Enhancing Slum Settlement Study Case: Tegal Sari Mandala III, Medan Denai District - Shaumira, Hanifah; Aulia, Dwira Nirfalini (Jurnal Koridor, 2024)
Tegal Sari Mandala III in the Medan Denai District is a residential area characterized by poor sanitation and a high risk of flooding, making it a mild slum. To prevent slum conditions from becoming normalized in Indonesian society, it is essential to address and eliminate such settlements. Each location presents unique challenges and requires tailored solutions to tackle slum issues effectively. This research employs both qualitative and quantitative methods, which are suitable for examining slum areas. The analysis reveals that the primary problems include poor environmental maintenance, such as garbage accumulation and improper waste management, leading to flooding, polluted rivers, and foul-smelling surroundings. Solutions to these issues include developing and enhancing the settlement quality by establishing a night market and creating green spaces along the banks of the Sulang Saling River.